Status of Taenia solium cysticercosis and predisposing factors in developing countries involved in pig farming - Kungu, Joseph M.; Dione, Michel M.; Ocaido, M.; Ejobi, F. (2015)
Taenia solium cysticercosis is a disease of pigs and humans populations considered endemic in many developing countries of Latin America, Africa, and South East Asia having serious impact on public health and agriculture. We conducted an in-depth comparative analysis of literature on the disease situation and predisposing factors in selected countries known to be at the interface of poverty-emerging livestock systems-zoonoses and with a growing small holder pig industry. Transmission, methods of diagnosis and employed control strategies of T. solium infection in pig and human populations in these countries are also discussed. Limited knowledge on porcine cysticercosis (PC) by various stakeholders expected to be key players in its control has undermined efforts for eliminating this potentially eradicable condition. Poor pig production practices, poor hygiene, and sanitation habits have also been important in the maintenance of the T. solium life-cycle. The major gaps identified in this review include scanty current information on PC prevalence in pigs with hardly any reports on the condition in humans in most developing countries. Factors affecting pattern of the infection and how they interact at the different levels of the pig value chain have not been exhaustively studied. Information on socioeconomic and public health impact is inadequate and not current.